2022
DOI: 10.1155/2022/8646724
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Pregnancy and Associated Factors among Women Who Live in Ilu Gelan District, Western Ethiopia, 2021

Abstract: Background. The World Health Organization Report noted that unintended pregnancy is the most common cause of maternal mortality in developing countries. Most unintended pregnancies occur where access to maternal care is limited, and because of this, many mothers lose their life. Therefore, this study was an attempt to assess the proportion of unintended pregnancy and associated factors among women who live in Ilu Gelan District, Western Ethiopia, 2021. Method. A community-based cross-sectional study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…For instance, a study conducted in the central portion of the country revealed that the prevalence of unintended pregnancy was 41.5% [ 5 ]. Other studies also reached a similar conclusion were; Gelan District (55%) [ 6 ] Hadiya zone(36%) [ 7 ], Gondar city (47%) [ 8 ], and Harari (33%) [ 9 ]. The consequences of unintended pregnancy are eclampsia, preeclampsia, and hemorrhage after birth, relative to planned pregnancy [ 10 ].…”
Section: Introductionsupporting
confidence: 61%
“…For instance, a study conducted in the central portion of the country revealed that the prevalence of unintended pregnancy was 41.5% [ 5 ]. Other studies also reached a similar conclusion were; Gelan District (55%) [ 6 ] Hadiya zone(36%) [ 7 ], Gondar city (47%) [ 8 ], and Harari (33%) [ 9 ]. The consequences of unintended pregnancy are eclampsia, preeclampsia, and hemorrhage after birth, relative to planned pregnancy [ 10 ].…”
Section: Introductionsupporting
confidence: 61%
“…According to recent studies conducted around the world, socio-demographic factors such as 5–10 household size, 5,11,12 level of education of the mother, 5,7,9,13 marital status, 5,10,11,14,15 income/wealth status, 3,7,16,17 distance from the nearest health facility, 15 parity, 3,5,9,10,13,14,18 knowledge of ovulation cycle, 12,18 ever had of terminated pregnancy, 6,8,14 birth interval, 16 not being primary decision maker, 19,20 knowledge of family planning, 13,16 residence, 3,13,17,19 region, 3,5,9,12,17 antenatal care (ANC) follow-up of previous pregnancy, 19 obstetric history, 20 community education about maternal health care, 19,20 health care provider support, 20 and complication during index pregnancy have a significant association with unintended pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…4 A multilevel analysis of 2016 Ethiopia Demographic and Health Survey (EDHS) data revealed that the prevalence of unintended pregnancy was 26.6%. 5 According to recent studies conducted around the world, socio-demographic factors such as [5][6][7][8][9][10] household size, 5,11,12 level of education of the mother, 5,7,9,13 marital status, 5,10,11,14,15 income/wealth status, 3,7,16,17 distance from the nearest health facility, 15 parity, 3,5,9,10,13,14,18 knowledge of ovulation cycle, 12,18 ever had of terminated pregnancy, 6,8,14 birth interval, 16 not being primary decision maker, 19,20 knowledge of family planning, 13,16 residence, 3,13,17,19 region, 3,5,…”
Section: Introductionmentioning
confidence: 99%
“…This study nding is less than the study conducted in Gellan [42], South Africa [43], Botswana [44], Arsi, Ethiopia[28], Ghana [21], Addis Ababa [45] and Debere Markos [46]. The discrepancy might be due to study population and study period variation, study area difference, methodological variation, difference of maternal health quality, coverage and accessibility including family planning methods, and socio-cultural.…”
Section: Discussionmentioning
confidence: 64%